Pancreatic Neuroendocrine Tumor with Extensive Intraductal Invasion of the Main Pancreatic Duct: A Case Report - Kiyonaga, Maki; Matsumoto, Shunro; Mori, Hiromu; Yamada, Yasunari; Takaji, Ryo; Hijiya, Naoki; Yoshizumi, Fumitaka; Aramaki, Masanori (JOP. Journal of the Pancreas, 2014)
Context Pancreatic neuroendocrine tumors account for only 1-3% of all pancreatic neoplasms and the intraductal invasion of the main pancreatic duct (MPD) is rare. Case report We report a case of a 26-year-old woman with an endocrine tumor of the pancreas extensively invading into the MPD. She presented abdominal pain and her laboratory data showed abnormal liver function. Contrast-enhanced computed tomography demonstrated a well-enhanced mass on the arterial dominant phase in the head of the pancreas. The mass grew within the lumen of the MPD in the body of the pancreas, with dilatation of the upstream MPD. The contrast-enhancement pattern between the main tumor of the head and the intraductal lesion of the body was different. On T2-weighted magnetic resonance (MR) imaging, the pancreatic head lesion showed non homogeneously low signal intensity, while the intraductal lesion of the pancreatic body showed high signal intensity. MR cholangiopancreatography showed obstruction of the MPD in the pancreatic head to body, with dilatation of the upstream MPD. An endocrine tumor or acinar cell carcinoma of the pancreas was considered as preoperative diagnosis, and pancreaticoduodenectomy was performed. As a result, pancreatic endocrine tumor (G2) was confirmed pathologically. Conclusion A rare case of pancreatic neuroendocrine tumor with extensive growth within the MPD was presented. The intraductal extension is a unique growth pattern of nonfunctioning pancreatic neuroendocrine tumor, and the desmoplastic reaction in this tumor may reflect the increased invasiveness. Image: Histopathological findings (H&E stain). The pancreatic head lesion is comprised of small nests and cords of uniform cells.